Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Biodiversity and biogeographic patterns of Nereididae (Annelida) across the Indo-Pacific Convergence Zone - Jieyang Weng; Xuwen Wu; Tiantian Wang; Chenrui Li; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

A transferable approach to assessing green infrastructure types (GITs) and their effects on surface urban heat islands with multi-source geospatial data - Linlin Lu; Huadong Guo; Qihao Weng; Carlos Bartesaghi-Koc; Paul Osmond; Qingting Li (Remote Sensing of Environment, 2024)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.